CuxS thin films for printed memory cells and temperature sensors. (1st June 2022) - Jehn, Johannes; Kaiser, Michael; Eulenkamp, Constanze; Moosheimer, Ulrich; Ruediger, Andreas; Schindler, Christina
Abstract: Printed electronics require a multitude of various inks for different applications which leads to compatibility issues for their integration. We present a procedure to deposit a thin layer of Cu x S via inkjet printing of Na2 S a q on a thermally grown or inkjet-printed Cu surface that provides applications in electrochemical metallization memory cells (ECMs) or temperature sensors. The nanosized transformation from Cu to Cu x S is investigated via confocal microscopy, scanning electron microscopy (SEM), as well as energy-dispersive x-ray spectroscopy (EDX). We analyze individual responses from the sensor and memory and evaluate their respective potential in printed electronics. The negative temperature coefficient of the semiconducting Cu x S is determined to be β 25, 80 = ( 656 ± 5 ) K. Resistive switching is observed for a current compliance between 0.1 and 1000 µ A, with a resistance ratio R O F F /R O N up to 10 5 . The use of the same inks and processes for the memory and sensor components paves the way for new and customized designs for smart logistics applications where temperature monitoring is required.